Pengaruh religiositas terhadap kesehatan mental: Integrasi perspektif psikologi dan agama islam - Zulfa, Intan Nala (Maliki Interdisciplinary Journal, 2026)
This paper discusses the relationship between religiosity and mental health through the integration of psychological and Islamic perspectives. Religiosity is understood as an individual’s involvement in beliefs, worship practices, spiritual experiences, religious knowledge, and their implications in daily life. Meanwhile, mental health refers to a state of psychological well-being that enables individuals to manage their emotions, cope with stress, and function optimally in social life. This study shows that religiosity can act as a protective factor for mental health through several psychological mechanisms, such as meaning-making, religious coping strategies, social support from religious communities, and self-regulation through spiritual practices. In the Islamic perspective, values such as tawakal (trust in God), sabar (patience), syukur (gratitude), and ikhlas (sincerity) have an important contribution in building mental well-being. The integration of empirical psychological approaches and Islamic spiritual values results in a more holistic understanding of human mental health. The findings of the study show that higher levels of religiosity tend to correlate with better psychological conditions, such as lower levels of stress, anxiety, and depression, as well as increased well-being. Therefore, an approach that combines psychological and spiritual aspects is considered relevant for developing a more comprehensive mental health intervention model, especially in communities with a strong religious background.